Grating‐based holographic diffraction methods for X‐rays and neutrons: phase object approximation and dynamical theory. Issue 1 (3rd January 2018) - Feng, Hao; Ashkar, Rana; Steinke, Nina; Dalgliesh, Robert; Lavrik, Nickolay V.; Kravchenko, Ivan I.; Pynn, Roger
Abstract : This paper presents a comparison of grating‐based holography using X‐rays and neutrons and tests the validity of analysis methods based on a weak phase approximation. Abstract : A method dubbed grating‐based holography was recently used to determine the structure of colloidal fluids in the rectangular grooves of a diffraction grating from X‐ray scattering measurements. Similar grating‐based measurements have also been recently made with neutrons using a technique called spin‐echo small‐angle neutron scattering. The analysis of the X‐ray diffraction data was done using an approximation that treats the X‐ray phase change caused by the colloidal structure as a small perturbation to the overall phase pattern generated by the grating. In this paper, the adequacy of this weak phase approximation is explored for both X‐ray and neutron grating holography. It is found that there are several approximations hidden within the weak phase approximation that can lead to incorrect conclusions from experiments. In particular, the phase contrast for the empty grating is a critical parameter. While the approximation is found to be perfectly adequate for X‐ray grating holography experiments performed to date, it cannot be applied to similar neutron experiments because the latter technique requires much deeper grating channels.